Baseline utilisation of specialist disability services in Ireland - Aoife Brick; Conor Keegan; Maev-Ann Wren (The Economic and Social Research Institute (ESRI), 2019)
The objective of this paper is to analyse the data on specialist disability services available in Ireland. The paper provides a baseline utilisation profile of selected services which can be used to project future service demand and expenditure. The limitations of the currently available data in providing a comprehensive picture of specialist disability services in Ireland are also outlined.
Keywords: 330